On the Clock Paradox - Abdesselam, A. (European Scientific Journal, ESJ, 2016)
Special Relativity presents before us several thought challenging paradoxes. The most famous one is the clock or twin paradox which arises from the well-known time dilation phenomenon. In this paper, we will give a brief but pedagogical treatment of this paradox. The crucial point is that the relativity of simultaneity, for events happening at different places, plays a fundamental role in understanding the apparent disagreement between the rest and the moving observers. Once this has been taken care of, the disagreement and the paradox would disappear.